Landslide hazard assessment and agricultural vulnerability using a geospatial approach - Girsang, Rian Gabriel; Simanjuntak, Bistok Hasiholan (Universitas Lancang Kuning, 2024)
The village of Cukilan, Semarang Regency, Indonesia, is predominantly utilized for agricultural purposes, facilitated by its high rainfall suitable for various crops. Despite the benefits it provides to farmers, the elevated rainfall also poses natural disaster risks, particularly landslides, which can adversely affect surrounding communities. This study aims to map landslide potentials and evaluate their impacts on the agricultural sector in the Cukilan Village, Semarang Regency. The research methodology encompasses a literature review focusing on landslide potential estimation and field survey. The literature review aims to obtain landslide potential distribution maps compiled by DVMBG, considering rainfall, slope, geology, land use, and soil types. Field surveys validate conditions based on landslide potential estimations, involving random soil sampling and analyzing parameters like permeability, texture, bulk density, depth, and surface density. The research findings reveal the impact of landslide potential on the agricultural sector and the mapping of landslide potential areas in Cukilan Village, depicting various risk levels: very high (0.71% of total area, covering 5 ha), high (13.24%, 93 ha), moderate (56.55%, 397 ha), and low (29.48%, 207 ha). Based on these findings, it is evident that managing landslide disaster risks in agricultural development in the area is crucial, including the implementation of safer land use planning and appropriate mitigation strategies.